THE ROLE OF TEACHER EFFICACY OVER ENGLISH LANGUAGE TEACHING - Esen Aslan YAZICI (Ömer Gökhan Ulum, 2019)
The main purpose of this study is to examine teacher efficacy levels of English language teachers who work in secondary schools. Also, teachers' self -reported English proficiency level and use of pedagogical strategies were investigated. Based on a quantitative study, the data were collected through three different questionnaires from 28 English language teachers. Results showed that teacher efficacy has an impact on teaching English. The data indicated that teachers' beliefs in their ability were correlated with their self-reported English proficiency. It was found that most of the teachers use communicatively oriented instructional strategies in the classroom. This study provides necessary and useful information to understand teachers' needs to develop their efficacy.